AN INDONESIAN BEAUTY STORY: HOW COLLEGE WOMEN IN INDONESIA REPRESENT BEAUTY, BODY IMAGE, AND SOCIAL MEDIA - Ajeng Azani Dwi Utami; Annisa Kurnia Hikmawati; Fadiya Sunaryo (JURNAL DARMA AGUNG, 2023)
The increasing use of social media today can influence how modern society defines body image and beauty standards. The research aims to describe how Indonesian women view beauty and body image through Instagram and to define the meaning of beauty from the perspective of Indonesian female students in the new media era. The method used is a qualitative method based on in-depth interviews. The participant were three female students from various universities in Indonesia, with different ethnicities and grew up in different cities. They are interested in the beauty industry and follow several beauty influencers. The results obtained shows that there has been a shift in values and culture towards the beauty standards of Indonesian women students due to the use of Instagram. The participants believe that skin color does not always need to have a fair complexion such as that of many South Koreans and Japanese, but smooth, clean and bright skin became the standard of beauty for them. Today's beauty ideals are influenced by the presence of beauty influencers on Instagram. Participants agreed that much of the Indonesia's ideal beauty resembles a beauty influencer whose face is a mixture of Indonesian and Western physical characteristics. College women who are currently considering cosmetic surgery are no longer viewed as taboo. Following beauty influencers without considering religious and cultural elements that prohibit cosmetic surgery to beautify their appearance is now commonplace for some women in Indonesia. The conclusion of the study shows that the social media Instagram has a significant influence on the representation of ideal beauty standards and women’s body image that is dreamed of by women participating in this study.